Simplify: `x^5/3(x^7/3-x^7/2)`

2 Answers | Add Yours

justaguide's profile pic

Posted on

The expression `x^5/3(x^7/3-x^7/2)` has to be simplified.

`x^5/3(x^7/3-x^7/2)`

=> `x^5/3((2x^7-3x^7)/6)`

=> `(x^5/3)*(-x^7/6)`

=> `-x^12/18`

The given expression `x^5/3(x^7/3-x^7/2)` = `-x^12/18`

oldnick's profile pic

Posted on

`x^5/3` `(x^7/3-x^7/2)=x^5/18(6x^7/3-6x^7/2)=x^5/18(2x^7-3x^7)=x^5/18(-x^7)=`

`=-x^(5+7)/18=-x^12/18`

``

We’ve answered 330,494 questions. We can answer yours, too.

Ask a question